2015
DOI: 10.1095/biolreprod.115.128942
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Model of Tubulobulbar Complex Internalization During Junction Remodeling in the Seminiferous Epithelium of the Rat Testis1

Abstract: Tubulobulbar complexes (TBCs) are elongate subcellular machines responsible for internalizing intercellular junctions during sperm release. Each complex consists of a double-membrane tubular core terminating in a clathrin-coated pit. The core is surrounded by a network of actin filaments, and a distinct swelling or bulb, which lacks an association with actin, develops in the distal third of the structure. The bulb eventually buds from the complex and enters endocytic compartments of the Sertoli cell. The relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Surface area of the Sertoli cell plasma membrane is increased dramatically by the extension of these arms, up to 16,000 μm 2 , showing tremendous stage‐dependent variation that involves the translocation of numerous organelles, the expression of hundreds of different classes of proteins for specific functions, and requiring the transport of these proteins to specific regional positions throughout the cycle of the seminiferous epithelium (Parvinen, , ; Ritzen et al ., ; Mather et al ., ; Wright et al ., , ; Parvinen et al ., ; Kaipia et al ., ; Toppari et al ., ; Johnston et al ., ; Hess & Vogl, ; Wright, ). Without an understanding of such complex form, it would have been impossible to comprehend the numerous functional interactions that depend on the Sertoli cell plasmalemma, such as tight junctional complexes that comprise the blood–testis barrier, as well as sperm disengagement (spermiation) and phagocytosis of the residual body of leftover spermatid cytoplasm (Vogl et al ., ; Hess & Vogl, ; Lyon et al ., ).…”
Section: Morphology Of the Sertoli Cellmentioning
confidence: 97%
See 1 more Smart Citation
“…Surface area of the Sertoli cell plasma membrane is increased dramatically by the extension of these arms, up to 16,000 μm 2 , showing tremendous stage‐dependent variation that involves the translocation of numerous organelles, the expression of hundreds of different classes of proteins for specific functions, and requiring the transport of these proteins to specific regional positions throughout the cycle of the seminiferous epithelium (Parvinen, , ; Ritzen et al ., ; Mather et al ., ; Wright et al ., , ; Parvinen et al ., ; Kaipia et al ., ; Toppari et al ., ; Johnston et al ., ; Hess & Vogl, ; Wright, ). Without an understanding of such complex form, it would have been impossible to comprehend the numerous functional interactions that depend on the Sertoli cell plasmalemma, such as tight junctional complexes that comprise the blood–testis barrier, as well as sperm disengagement (spermiation) and phagocytosis of the residual body of leftover spermatid cytoplasm (Vogl et al ., ; Hess & Vogl, ; Lyon et al ., ).…”
Section: Morphology Of the Sertoli Cellmentioning
confidence: 97%
“…The regulation of ScTj proteins and structure is multifaceted, involving hormones such as androgens and FSH, cytokines (i.e., TNFα and TGFβ), the presence of germ cells, actin nucleating protein N‐WASP (neuronal Wiskott‐Aldrich syndrome protein), and phosphorylation of key proteins such as the claudins (Mruk & Cheng, ). In addition, a basal tubulobulbar complex has been identified morphologically as a potential component of the assembly and disassembly that is required for passage of the early spermatocytes through the ScTj (Du et al ., ; Lyon et al ., ). The current hypothesis is that this activity provides a remodeling of the intercellular junctions and disengagement of junctional molecules in the plasma membrane, followed by endocytosis and intracellular trafficking (Du et al ., ; Lyon et al ., ; Mruk, ).…”
Section: Morphology Of the Sertoli Cellmentioning
confidence: 97%
“…2a), we noticed intense punctate immunoreactivity with the A antibody in apical regions of Sertoli cells, where spermatids are released and the ER forms specialized contacts to the plasma membrane within the so called tubulobulbar complexes (TBC). TBCs are unique to Sertoli cells and are clathrin-dependent subcellular structures required for internalization of intracellular junctions and membranes once spermatids are released 24,27,28 . At higher magnification, we observed that these punctate structures often contain a less stained lumen (arrows in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As each structure matures, a bulb begins to form near the end of the complex through the local loss of the actin‐network and the formation of an extensive membrane contact site with a cistern of ER. The bulb expands proximally and eventually undergoes scission near the base of the structure (Lyon et al, ). It is not entirely clear what happens to the distal tubules and clathrin‐coated pits at the end of the structures, but we suspect they likely are resorbed back into the bulbs prior to or during scission.…”
Section: Formation and Scissionmentioning
confidence: 99%
“…Actin filament networks are clearly major components of TBCs. Perturbation of the networks with the actin destabilizing drug cytochalasin either prevents the tubular elements of TBCs from forming (Russell et al, ), or results in short, dilated, and abnormally shaped TBCs (Lyon et al, ; Sriram et al, ). The results of these studies are consistent with the conclusion that actin is involved with the elongation and maintenance of the tubular components of TBCs.…”
Section: The Role Of Actinmentioning
confidence: 99%